Tirzepatide: A dual action approach to weight reduction and glycemic control in type 2 diabetes mellitus - Princy Domnic Dsouza; Sai Phalguna Prakash Chitralu; Ramish Khan; Sanatkumar Bharamu Nyamagoud (MGM Journal of Medical Sciences)
Tirzepatide, a dual GIP and GLP-1 receptor agonist, is an innovative therapy for type 2 diabetes mellitus (T2DM) and obesity. By stimulating insulin secretion, inhibiting glucagon release, slowing gastric emptying, and enhancing satiety, it offers superior glycemic control and weight reduction compared to conventional GLP-1 receptor agonists. Clinical trials, such as SURPASS and SURMOUNT, have demonstrated their effectiveness in lowering HbA1c and body weight, with potential benefits in conditions like NAFLD, PCOS, and cardiovascular health. While its therapeutic profile is promising, further research is needed to assess its long-term safety, particularly concerning cardiovascular outcomes, gastrointestinal effects, and the risk of medullary thyroid carcinoma (MTC). Its once-weekly administration improves adherence; however, cost and accessibility remain significant challenges. A personalized medicine approach, incorporating biomarker-driven patient selection, may enhance treatment outcomes. As research continues, tripeptide has the potential to revolutionize metabolic disease management. Future studies will clarify its long-term safety, cost-effectiveness, and broader clinical applications.